174k views
2 votes
Find the product of the following

(6x – 9)(5x + 4)
(3x2 + 2x)(x – 6)
(2x2 – 5x + 3)(4x3 – 1)

User StapleGun
by
5.4k points

1 Answer

5 votes
Use FOIL. (First, Outside, Inside, Last). Remember to combine like terms afterwards.

(6x - 9)(5x + 4)

(6x)(5x) = 30x²
(6x)(4) = 24x
(-9)(5x) = -45x
(-9)(4) = -36

30x² + 24x - 45x - 36

combine like terms

30x² + (24x - 45x) - 36 => 30x² - 21x - 36 (answer)

-------------------------------------------------------------------------------------------------------

(3x² + 2x)(x - 6)

3x²(x) = 3x³
3x(-6) = -18x
2x(x) = 2x²
2x(-6) = -16x

Combine like terms

3x³ + 2x² - 18x - 16x

3x³ + 2x² - 34x is your answer

-------------------------------------------------------------------------------------------------------

(2x² - 5x + 3)(4x³ - 1)

FOIL: Distribute each number in one parenthesis to all monomials in the other

4x³(2x²) = 8x^5
4x³(-5x) = -20x^4
4x³(3) = 12x³
-1(2x²) = -2x²
-1(-5x) = 5x
-1(3) = -3

8x^5 - 20x^4 +12x³ - 2x² + 5x -3 is your answer

-------------------------------------------------------------------------------------------------------

hope this helps
User PKKid
by
5.5k points